Credit unions and its position within the cooperative model. Integration versus differentiation in the framework of the financial system reform - Vargas Vasserot, Carlos (REVESCO. Revista de Estudios Cooperativos, 2015)
In this paper will be analyzed the legal framework of Credit Unions, presenting its origin on the half of the nineteenth century in the territory which is called now Germany and the reception and evolution of the institution in Spain to reach the current troubled situation in which, after the financial crisis experienced in recent years, is intensely debated what the future of the sector should be with an announced reform of its legal system.
Keywords: credit unions; rural credit banks; Raifeissen; financial system reform; integration; credit cooperative; financial crisis